Efficacy of the combination rifampin-streptomycin in preventing growth of Mycobacterium ulcerans in early lesions of Buruli ulcer in humans - Etuaful, S.; Carbonnelle, B.; Grosset, J.; Lucas, S.; Horsfield, C.; Phillips, R.; Evans, M.; Ofori-Adjei, D.; Klustse, E.; Owusu-Boateng, J.et.al. (Antimicrobial Agents and Chemotherapy, 2005)
Mycobacterium ulcerans disease is common in some humid tropical areas, particularly in parts of West Africa, and current management is by surgical excision of skin lesions ranging from early nodules to extensive ulcers (Buruli ulcer). Antibiotic therapy would be more accessible to patients in areas of Buruli ulcer endemicity. We report a study of the efficacy of antibiotics in converting early lesions (nodules and plaques) from culture positive to culture negative. Lesions were excised either immediately or after treatment with rifampin orally at 10 mg/kg of body weight and streptomycin intramuscularly at 15 mg/kg of body weight daily for 2, 4, 8, or 12 weeks and examined by quantitative bacterial culture, PCR, and histopathology for M. ulcerons. Lesions were measured during treatment. Five lesions excised without antibiotic treatment and five lesions treated with antibiotics for 2 weeks were culture positive, whereas three lesions treated for 4 weeks, five treated for 8 weeks, and three treated for 12 weeks were culture negative. No lesions became enlarged during antibiotic treatment, and most became smaller. Treatment with rifampin and streptomycin for 4 weeks or more inhibited growth of M. ulcerons in human tissue, and it provides a basis for proceeding to a trial of antibiotic therapy as an alternative to surgery for early M. ulcerons disease. Copyright © 2005, American Society for Microbiology. All Rights Reserved.
Keywords: Rifampin-streptomycin; Mycobacterium ulcerans; Buruli ulcer